Method for evaluating performance of regenerated graphite material in lithium ion battery

By drying and baking the recycled graphite material at high temperature and mixing it with the electrolyte, and using a spectrophotometer to determine the color change of the solution, the problem of long and high cost of performance evaluation of recycled graphite materials in the prior art is solved, and a fast and accurate performance evaluation is achieved.

CN120275313APending Publication Date: 2025-07-08ZHEJIANG NARADA POWER SOURCE CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510511175.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-23
Publication Date
2025-07-08

AI Technical Summary

Technical Problem

In the prior art, the performance evaluation method for recycled graphite materials in lithium-ion batteries takes a long time and is costly, making it difficult to meet the company's rapid detection needs.

Method used

By drying the recycled graphite material, mixing it with the electrolyte and baking it at high temperature, the color change of the solution is measured by using a spectrophotometer, its performance is quickly evaluated, and oxidative impurities and defect structures are identified.

Benefits of technology

It realizes rapid and accurate evaluation of the electrical performance of recycled graphite materials in lithium-ion batteries, reducing detection costs and time, and improving detection efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
Patent Text Reader

Abstract

The invention discloses a method for evaluating the performance of a regenerated graphite material in a lithium ion battery, and belongs to the technical field of lithium ion batteries. The invention discloses a method for evaluating the performance of a regenerated graphite material in a lithium ion battery. The method comprises the following steps: S1, drying the regenerated graphite material to reduce the moisture content; s2, mixing the dried regenerated graphite material with an electrolyte, sealing and then baking; s3, taking out the turbid liquid obtained after baking, and standing for natural sedimentation; and S4, taking the settled supernatant and testing the absorbance. According to the method for evaluating the performance of the regenerated graphite material in the lithium ion battery, the number of existing oxidizing impurity groups and the number of defect structures of a graphite body are quantitatively recognized through a spectrophotometer, so that the electrical performance of the lithium ion battery prepared from the material is judged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and particularly to a method for evaluating the performance of recycled graphite materials in lithium-ion batteries. Background Art

[0002] Compared with other secondary batteries, lithium-ion batteries have the advantages of high energy density, no memory effect, low self-discharge rate, long cycle life, and fast charging ability, and are thus widely used in many fields such as smartphones, laptops, electric vehicles, and energy storage systems. And with the expansion of the production scale and the improvement of the technical maturity of lithium-ion batteries, the installed capacity of lithium-ion batteries is getting larger and larger. Lithium-ion batteries have a certain limit on the number of charge-discharge cycles. As the usage time increases and the number of charge-discharge cycles increases, the battery performance will gradually decline. When the battery capacity drops below 80% of the original capacity, the battery is usually considered to have reached its service life and needs to be replaced.

[0003] With the rapid development of electric vehicles and energy storage systems, the scrap volume of lithium-ion batteries (LIBs) has increased sharply. Lithium-ion batteries contain high-value metals such as lithium, cobalt, and nickel, as well as recyclable materials such as graphite and electrolyte. Their resource regeneration (recovery and reuse) has become the focus of global attention. The resource regeneration of lithium-ion batteries is not only an inevitable choice to cope with resource shortage and environmental pollution, but also a new track for industrial chain competition in the global energy transformation. With the emergence of technological breakthroughs and scale effects, the regeneration of lithium-ion battery resources is expected to transform from a "cost center" to a "profit center", promoting the global new energy industry to upgrade to a zero-waste circular model.

[0004] As the main material of the negative electrode of lithium-ion batteries (accounting for 10%-15% of the total battery mass), the recycling and reuse of graphite is of great significance for reducing resource consumption, reducing carbon emissions, and improving economic efficiency. The European Union's "New Battery Law" requires that the proportion of recycled materials in batteries reach 12% by 2030, promoting car manufacturers to purchase recycled graphite. The carbon emission intensity of recycled graphite (about 3 kg CO2 / kg) is significantly lower than that of artificial graphite (15-20 kg CO2 / kg), which conforms to the ESG investment trend. In the next 5-10 years, graphite recycling may become a new growth pole in the field of lithium-ion battery resource recovery, promoting the industry to shift from a "metal-centered" to a "full material cycle" sustainable development model.

[0005] Currently, the recycling of graphite for lithium-ion batteries mainly separates graphite from components such as copper foils and binders through means such as crushing, screening, and flotation, and then purifies it by pickling to leach out metal impurities. The current evaluation of recycled graphite is directly carried out by indirectly judging through testing the battery cells after manufacturing them. This method has a long time-consuming cycle and high testing costs, and it is difficult to meet the time requirements of incoming material inspection and the cost control requirements of enterprises. Therefore, a more efficient and practical method is needed to detect the performance of batch samples of recycled graphite in batteries. Summary of the Invention

[0006] Aiming at the characteristics of recycled graphite materials, the purpose of the present invention is to provide a method for pre-evaluating the performance of recycled graphite materials in lithium-ion batteries.

[0007] Through research and analysis of the production process of recycled graphite, it is identified that certain oxidative impurities may be introduced during the crushing and pickling purification processes of recycled graphite materials, and certain defect structures are formed in the graphite body, resulting in a certain degree of performance degradation of the battery cell products made of this material.

[0008] The present invention discloses a method for evaluating the performance of recycled graphite materials in lithium-ion batteries, including the following steps:

[0009] S1: Dry the recycled graphite material to reduce the moisture content;

[0010] S2: Mix the dried recycled graphite material with the electrolyte, seal it, and bake it;

[0011] S3: Take out the suspension obtained after baking and let it settle naturally;

[0012] S4: Take the supernatant after sedimentation and test the absorbance.

[0013] Quickly evaluate the performance of graphite materials in lithium-ion batteries according to the absorbance index. The smaller the absorbance, the better the performance of the recycled graphite material, and the larger the absorbance, the worse the electrical performance of the recycled graphite material.

[0014] Due to the body defects or the presence of oxidative impurities in recycled graphite, certain side reactions will occur after it comes into contact with the electrolyte. During the high-temperature baking process after mixing recycled graphite and the electrolyte, the side reactions will be accelerated, resulting in a color change in the mixed solution. This color change is reflected in the depth of the color due to the different degrees of the reaction. Under the condition that other variables are the same, the degree of the reaction is positively correlated with the body defects of recycled graphite or the content of oxidative impurities. Therefore, the depth of the solution color is quantitatively measured by a spectrophotometer to evaluate the quality of the electrical performance of recycled graphite materials.

[0015] Further, in step S1, the drying temperature is 80 - 105 °C, and the drying time is 8 - 12 h.

[0016] Further, the moisture content of the dried regenerated graphite material is ≤ 1 ppm.

[0017] Reduce the moisture content of the regenerated graphite material to reduce the interference of moisture during the test.

[0018] Further, in step S2, the electrolyte includes a lithium salt and a solvent; the lithium salt includes at least one of LiPF6 (lithium hexafluorophosphate), LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium trifluoromethanesulfonimide), LiBOB (lithium bis(oxalato)borate), LiBF4 (lithium tetrafluoroborate); the solvent includes at least two of ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC).

[0019] Further, the concentration of the lithium salt is 0.8 - 1.5 mol / L; in the solvent, the volume ratio of ethylene carbonate, ethyl methyl carbonate, dimethyl carbonate, and diethyl carbonate is (30 - 40):(25 - 70):(0 - 30):(0 - 30).

[0020] Further, in step S2, the dried regenerated graphite material and the electrolyte are mixed at a mass ratio of 1:(3 - 9).

[0021] Further, in step S2, the baking temperature is 55 - 85 °C, and the baking time is 3 - 10 days.

[0022] Further, in step S3, the temperature for natural sedimentation is 20 - 30 °C, and the sedimentation time is 1 - 3 days.

[0023] Further, in step S4, the wavelength for absorbance measurement is 350 - 600 nm.

[0024] Further, the comparison of absorbance values is carried out within two wavelength ranges of 370 ± 5 nm and 455 ± 5 nm.

[0025] A method for evaluating the performance of a regenerated graphite material in a lithium-ion battery provided by the present invention strictly controls the moisture of the graphite material, and after mixing with the electrolyte, high-temperature baking is carried out to accelerate the occurrence of side reactions between the regenerated graphite material and the electrolyte, so as to identify the oxidative impurity groups and the defect structure of the graphite matrix existing in the regenerated graphite material in a short time, and creatively quantitatively identify the amount of oxidative impurity groups and the defect structure of the graphite matrix through a spectrophotometer, thereby judging the electrical performance of the lithium-ion battery prepared using this material. Description of the Drawings

[0026] Figure 1 It is the absorbance test result diagram of Examples 1-4 in the present invention;

[0027] Figure 2 It is the cycle test result diagram of the lithium-ion battery assembled with the graphite material of Examples 1-4 in the present invention. Detailed implementation manners

[0028] To make the technical solution of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0029] Instruments used for absorbance test:

[0030] Instrument name: UV-Visible Intelligent Multi-parameter Water Quality Detector.

[0031] Instrument model: LH-3BA (V12).

[0032] Wavelength range: (190 - 1100) nm, covering a wide range from ultraviolet to visible light, meeting various analysis requirements.

[0033] Spectral bandwidth: 2.0 nm, ensuring high resolution and accuracy of measurement.

[0034] Wavelength resolution: 0.1 nm, achieving high-precision wavelength resolution ability.

[0035] Baseline flatness: ≤±0.002 A, ensuring the stability of the baseline and the accuracy of the measurement results.

[0036] Working environment: Adapt to an ambient temperature of (5 - 40) °C and an ambient humidity of ≤85% RH (no condensation). The rated voltage is AC220V ± 10% / 50Hz, and the rated power is 80W.

[0037] The method for recycling graphite materials is as follows:

[0038] 1. Disassemble the used lithium-ion battery and take out the negative electrode sheet.

[0039] 2. Immerse the negative electrode sheet in an organic solvent (such as N-methylpyrrolidone) and assist with ultrasonic treatment to dissolve the binder, achieving the separation of the graphite material from the current collector copper foil.

[0040] 3. Pickle the separated graphite material with an acid solution such as dilute hydrochloric acid or dilute sulfuric acid to remove metal impurities such as iron and copper. After pickling, repeatedly rinse the graphite material with deionized water until the rinsing solution is neutral to remove the residual acid solution and impurity ions. After vacuum drying to remove moisture, the preliminarily treated graphite material is obtained.

[0041] 4. Put the preliminarily processed graphite material into a high-temperature furnace and conduct high-temperature treatment under the protection of an inert gas (such as argon). The temperature is generally between 1000 - 1500 °C. Through high-temperature treatment, the crystal structure of graphite can be repaired, residual organic substances and impurities can be removed, and the purity and crystallinity of graphite can be improved.

[0042] Example 1

[0043] Recycled graphite sample: numbered RG-1.

[0044] Specific operation steps:

[0045] Weigh 5 g of the RG-1 sample and place it in an oven at 90 °C for 10 h to test the water content C H2O (qualified when ≤1 ppm). Prepare an electrolyte solution of 1.2 mol / L (where the lithium salt is LiPF6, the solvents are EC, EMC, and DMC, and the volume ratio of EC:EMC:DMC in the solvents is 3:5:2). Take 30 g of the electrolyte sample and mix it with 5 g of the dried RG-1 sample in a glass bottle and seal it to obtain a suspension sample. Place the above suspension sample in an oven at 85 °C and let it stand for 120 h, then take it out and let it stand at 25 °C for natural sedimentation for 24 h. Use a pipette to transfer the supernatant of the suspension and then place it in a cuvette for use.

[0046] Debug the instrument: Run the LH-3BA (V12) ultraviolet-visible intelligent multi-parameter water quality detector, perform the instrument self-check program, and preheat the system so that the electronic components and light source of the instrument reach the best measurement state. Click the ultraviolet-visible spectrophotometer icon on the control panel to enter this measurement mode. Take a standard platinum-cobalt solution sample of 5 Hazen and conduct repeated absorbance tests 10 times. The relative standard deviation of the maximum absorbance values within the two wavelength ranges of 370 ± 5 nm and 455 ± 5 nm is less than 1% as qualified;

[0047] Obtain the absorbance of the sample: Use the ultraviolet-visible intelligent multi-parameter water quality detector to scan and test the sample under the set conditions, perform moving average smoothing on the curve, obtain the wavelength-absorbance curve graph of the sample (as Figure 1 shown), and perform peak searching and marking. The results are shown in Table 1.

[0048] Example 2

[0049] The difference between Example 2 and Example 1 is only that the batch of recycled graphite material used is different, and the number is RG-2.

[0050] Example 3

[0051] The difference between Example 3 and Example 1 is only that the batch of recycled graphite material used is different, and the number is RG-3.

[0052] Example 4

[0053] The difference between Example 4 and Example 1 is only that the batches of the regenerated graphite materials used are different, and the number is RG-4.

[0054] Table 1. Comparison of absorbance data of examples

[0055] Example Number Example 1 Example 2 Example 3 Example 4 Sample Number 1 (RG-1) 2 (RG-2) 3 (RG-3) 4 (RG-4) Absorbance A1 / Abs (370 ± 5 nm) 0.041 0.127 0.202 0.219 Absorbance A2 / Abs (455 ± 5 nm) 0.013 0.021 0.044 0.058

[0056] As Figure 1 shown in and Table 1, the absorbance sizes are as follows: Experimental Example 1 < Experimental Example 2 < Experimental Example 3 < Experimental Example 4. Therefore, the performance quality of the electrical properties after assembling into a lithium-ion battery should be: Experimental Example 1 > Experimental Example 2 > Experimental Example 3 > Experimental Example 4.

[0057] Verify the effectiveness of this method:

[0058] The charge test and cycle test of lithium-ion batteries are very important for their electrical properties. They provide key data for evaluating battery performance and help understand the performance of the battery in actual use. The regenerated graphite materials used in the tests of Examples 1-4 were respectively assembled into lithium-ion batteries for charge test and cycle test.

[0059] The specific operations are as follows:

[0060] Using LFP (lithium iron phosphate) as the positive electrode material, it is mixed with SP (conductive carbon black) and PVDF (polyvinylidene fluoride) at 96wt%:1wt%:3wt%, coated on aluminum foil, and after being die-cut by hardware, the positive electrode plate is obtained. Using the above regenerated graphite materials RG-1 / RG-2 / RG-3 / RG-4 as the negative electrode active materials respectively, SP (conductive carbon black), CMC (sodium carboxymethyl cellulose) and SBR (styrene-butadiene rubber latex) are mixed at 95wt%:1wt%:1.5wt%:2.5wt%, coated on copper foil, and after being die-cut by hardware, the negative electrode plate is obtained. The above positive and negative electrode plates are separated by a PP (polypropylene) separator and then laminated to obtain a dry battery cell, and a 30Ah soft-pack lithium-ion battery is obtained by injecting lithium-ion battery electrolyte.

[0061] Test the charge performance and cycle performance according to the following steps:

[0062] Charge test:

[0063] The battery cell is charged at a constant current and constant voltage of 0.5C until full charge, and discharged at 1C to 2.5V (record the discharge retention capacity at this step as Qbegin).

[0064] Normal temperature charged storage: Charge the battery cell at a constant current of 0.5C and constant voltage until full, leave it standing at normal temperature of 25°C for 28 days, discharge it at 1C to 2.5V (record the discharge retention capacity at this step as Q1), let it stand for 10 minutes, charge it at a constant current of 0.5C and constant voltage until full, let it stand for 10 minutes, and discharge it at 1C to 2.5V (record the discharge recovery capacity at this step as Q2);

[0065] High temperature charged storage: Charge the battery cell at a constant current of 0.5C and constant voltage until full, leave it standing at high temperature of 60°C for 7 days, discharge it at 1C to 2.5V (record the discharge retention capacity at this step as Q1), let it stand for 10 minutes, charge it at a constant current of 0.5C and constant voltage until full, let it stand for 10 minutes, and discharge it at 1C to 2.5V (record the discharge recovery capacity at this step as Q2);

[0066] Retention rate = Q1 / Qinitial; Recovery rate = Q2 / Qinitial. The test results are shown in Table 2.

[0067] Table 2. Charged test results

[0068] Retention Rate at 25°C for 28 Days Recovery Rate at 25°C for 28 Days Retention Rate at 60°C for 7 Days Recovery Rate at 60°C for 7 Days Experimental Example 1 97.1% 97.9% 96.5% 97.1% Experimental Example 2 95.9% 96.2% 95.3% 95.9% Experimental Example 3 92.2% 92.6% 91.5% 92.1% Experimental Example 4 88.3% 88.7% 86.7% 87.2%

[0069] As can be seen from Table 2, the excellent charging performance is ranked as follows: Experimental Example 1 > Experimental Example 2 > Experimental Example 3 > Experimental Example 4, and this order is consistent with Figure 1 the order of absorbance from small to large in [], indicating that the charging performance of the recycled graphite material has a strong correlation with the absorbance of the processed material samples in this scheme. The larger the absorbance, the worse the charging performance, and the smaller the absorbance, the better the charging performance.

[0070] Cycling test:

[0071] Charge the lithium-ion battery at a constant current of 1C and constant voltage until full, let it stand for 30 minutes, discharge it at 1C to 2.5V, let it stand for 30 minutes. This is one week of cycling. Repeat the above steps and record the capacity decay under different cycling weeks. Capacity (retention) ratio = discharge capacity after each step of cycling / initial capacity. The test results are as Figure 2 shown.

[0072] As Figure 2 can be seen, the excellent cycling performance is ranked as follows: Experimental Example 1 > Experimental Example 2 > Experimental Example 3 > Experimental Example 4, and this order is consistent with Figure 1 the order of absorbance from small to large in [], indicating that the cycling performance of the recycled graphite material has a strong correlation with the absorbance of the processed material samples in this scheme. The larger the absorbance, the worse the cycling performance, and the smaller the absorbance, the better the cycling performance.

[0073] The method for evaluating the performance of recycled graphite materials in lithium-ion batteries provided by the present invention can quantitatively detect the characteristics related to material performance with high accuracy; it can quickly evaluate the performance of materials applied in battery products, with short time consumption and low cost.

[0074] The embodiments described above merely represent several implementation manners of the present invention. The description thereof is relatively specific and detailed, but it should not be construed as a limitation to the scope of the patent of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the concept of the present invention, several modifications and improvements can still be made, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the appended claims.

Claims

1. A method for evaluating the performance of regenerated graphite materials in lithium-ion batteries, characterized in that, It includes the following steps: S1: Dry the recycled graphite material to reduce the moisture content; S2: Mix the dried recycled graphite material with the electrolyte, seal it and bake; S3: Take out the suspension obtained after baking and let it settle naturally; S4: Take the supernatant after settlement and test the absorbance.

2. The method for evaluating the performance of a regenerated graphite material in a lithium-ion battery according to claim 1, characterized in that In step S1, the drying temperature is 80 - 105 °C and the drying time is 8 - 12 h.

3. The method for evaluating the performance of a regenerated graphite material in a lithium-ion battery according to claim 2, wherein The moisture content of the dried recycled graphite material ≤ 1 ppm.

4. The method for evaluating the performance of a regenerated graphite material in a lithium-ion battery according to claim 1, wherein In step S2, the electrolyte includes a lithium salt and a solvent; the lithium salt includes at least one of LiPF6, LiFSI, LiTFSI, LiBOB, LiBF4; the solvent includes at least two of ethylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate.

5. The method for evaluating the performance of a regenerated graphite material in a lithium-ion battery according to claim 4, characterized in that The concentration of the lithium salt is 0.8 - 1.5 mol / L; in the solvent, the volume ratio of ethylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate is 30 - 40:25 - 70:0 - 30:0 - 30.

6. The method for evaluating the performance of a regenerated graphite material in a lithium-ion battery according to claim 1, characterized in that, In step S2, the dried recycled graphite material and the electrolyte are mixed in a mass ratio of 1:3 - 9.

7. A method for evaluating the performance of a regenerated graphite material in a lithium-ion battery according to claim 1, characterized in that, In step S2, the baking temperature is 55 - 85 °C and the baking time is 3 - 10 days.

8. The method for evaluating the performance of a regenerated graphite material in a lithium-ion battery according to claim 1, characterized in that, In step S3, the temperature for natural settlement is 20 - 30 °C and the settlement time is 1 - 3 days.

9. The method for evaluating the performance of a regenerated graphite material in a lithium-ion battery according to claim 1, characterized in that, In step S4, the wavelength for absorbance test is 350 - 600 nm.

10. A method for evaluating the performance of a regenerated graphite material in a lithium-ion battery according to claim 1, characterized in that The comparison of absorbance values is carried out within two wavelength ranges of 370 ± 5 nm and 455 ± 5 nm.